A Meth mouth case - Jerry E. Bouquot (Our Dermatology Online, 2014)
Darkly discolored, cariously destroyed teeth were "normal" 18 months previously. Methamphetamine, plus the lack of oral hygiene and craving for sweet foods and drinks, can destroy teeth in adults more rapidly than any other process.